BENTUK PENYAJIAN TARI JEPIN KEMBANG MANGGAR DI KELURAHAN BATU LAYANG KOTA PONTIANAK - Christiani Resha Pageans; Ismunandar Ismunandar; Regaria Tindarika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThe background of this research is to find out and understand more deeply the form of Jepin Kembang Manggar dance presentation in Batu Layang Subdistrict, North Pontianak District, which includes: dance movements, top design, floor design, dramatic design, dynamics, group composition, themes, musical accompaniment, cosmetology and fashion, property and venue.  This study uses descriptive methods in a qualitative form and uses a choreographic approach.  The results of this study are the dance name Jepin Kembang Manggar taken from the property name, manggar.  Jepin Kembang Manggar dance has an initial, middle and final motion.  Jepin Kembang Manggar dance is a group dance and can be danced en masse.  The musical instruments used to elevate the Jepin flower dance of Manggar are Gambus, Gendang Panjang, Tawak / Gong, Tar, Violin and Accordion.  Jepin Kembang Manggar dance, using realist makeup.  Clothing worn by female dancers, brackets, trousers, gills, obi, and flower accessories and earrings.  The clothing worn by male dancers uses a telok pot, gill cloths, and the slopes worn on the head.  The property used is the flower shaped Manggar. Keywords: Dance, Jepin Kembang Manggar, Presentation